ANALISIS PENDAPATAN PETANI SEBELUM DAN SESUDAH MENGIKUTI PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN DAN IDENTIFIKASI KEBERHASILAN PROGRAM DI KABUPATEN OGAN KOMERING ULU - Lastinawati, Endang (LPPM UBB, 2014)
ABSTRACTThis study aims to: (1) Calculating the farmers income before and after implementation Rural Agribusiness Development Program (RADP) in the District OKU. (2) Analyze the effectiveness of RADP in the District OKU based on indicators of success set out in the Minister of Agriculture. The experiment was conducted in the District OKU with sample location in the Village of Sepancar Lawang Kulon Eastern Baturaja District and the Village Karang Endah West Baturaja District, using the survey method. The sampling is done by using disproportioned random sampling method, as much as 29 samples from the Village of Sepancar Lawang Kulon and 21 samples from the Village of Karang Endah who participated in the RADP implementation in the District OKU year 2010. The results showed that the income of farmers increased in the district OKU, where farmers income before the program PUAP year 2009 amounted to Rp 21.425.639,00 increased to Rp 34.058.657,00 after the program PUAP year 2010. RADP in the District OKU can be said to be effective seen from the indicators of success that includes the success of the output, outcome, the benefits and impact.Keywords : farmersâ income, effectiveness, impact, agribusiness program